Atypical Midface Tumor Complicating Nevus of Ota - Patzwahl, René; Landau, Klara; Kollias, Spyros S. (American Journal of Neuroradiology, 2005)
Summary: In the differential diagnosis of midface masses, the nevus of Ota (also called oculodermal melanocytosis) is a rare entity. We present a case of a young white man, who lost his left eye function by progression of a melanocytotic lesion involving the ophthalmic (VI) and maxillary (VII) divisions of the trigeminal nerve. The time course, distribution along the trigeminal nerve, and characteristic MR signal intensities of the lesion, in correlation with the clinical, ophthalmological, and dermatological findings, point to the correct diagnosis.